Cadherin‐11 deficiency mitigates high‐fat diet‐induced inflammatory atrial remodeling and vulnerability to atrial fibrillation. Issue 8 (16th January 2021) - Fang, Guojian; Cao, Wei; Chen, Long; Song, Shuai; Li, Yingze; Yuan, Jiali; Fei, Yudong; Ge, Zhuowang; Chen, Yuhan; Zhou, Lei; Xiao, Ying; Wan, Yi; et al.
Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia nowadays. The occurrence of AF is closely associated with obesity. Cadherin‐11 (Cad‐11), as a member of the cadherin family, can make a contribution to diet‐induced obesity and it will be informative to know whether Cad‐11 exerts its effects on atrial remodeling and AF vulnerability in a diet‐induced obesity model. In this study, we demonstrated that the expression of Cad‐11 was significantly upregulated in the left atrium of AF patients with obesity and mice following 16 weeks of high‐fat diet (HFD) feeding. Further confirmed that Cad‐11 could regulate the activity of atrial fibroblasts by participating in inducing proinflammatory cytokines production. At animal levels, we found that although there was a lack of statistical difference in body weight, Cad‐11 −/− mice could markedly improve impaired glucose tolerance and hyperlipidemia. Adverse atrial structural remodeling, including atrial enlargement, inflammation, and fibrosis provoked by HFD feeding were mitigated in Cad‐11 −/− mice. Mechanistically, Cad‐11 activated mitogen‐activated protein kinases and nuclear factor‐κB for interleukin‐6 production in atrial fibroblasts that may contribute to the atrial fibrosis process in obesity‐related AF, suggesting Cad‐11 might be a new therapeutic target for obesity‐related AF. Abstract : In this paper, we, for the first time, report a cadherin adhesion molecule cadherin‐11 could make a contribution to diet‐induced obesity and further verified how this molecule functions in clinical samples, cells, and model animals through a mechanism that involves activation of mitogen‐activated protein kinase and nuclear factor‐κB signaling pathways, thus finding a new treatment strategy for the pathogenesis of obesity‐related atrial fibrillation.